LITERATURE OF THE EMERGENCY OF THE CROCODILE IN BELITUNG ISLAND - Dwi Agus Munandar (Akuatik: Jurnal Sumberdaya Perairan, 2020)
Crocodile attacks often occur in several areas in Belitung Island, especially in the estuaries of the river and the coast. Not available of the detail information related to the location of the appearance of crocodiles in Belitung Island is the background of this research. This research aimed to map the location of the appearance of crocodiles and identified the crocodile species in Belitung Island. This research method is descriptive with observation and interview approach. The results showed that there were 17 location points of crocodile appearance in Belitung Island, namely 2 points in Belitung Regency and 15 points in East Belitung Regency. Some crocodile habitats in Belitung Island, including in some waters such as Pilang River, Keladi River, Sembulu River, Nujau Lake, Lenggang River, Sambar River, Mirang River, and Kero Lake. The identification results showed that the types of crocodiles in Belitung Island are Estuarine Crocodile (Crocodylus porosus). Therefore, it is recommended to continue to maintain the condition of the waters ecosystem in Belitung Island so that the habit of crocodile remains sustainable.